Supporters of the changes in the teaching context and obstetric nursing practice - Torcata Amorim; Dulce Maria Rosa Gualda (Rev Rene)
The research aimed to find out which factors have facilitated the graduation and re-insertion of obstetrician nurses in parturition assistance since the 1980s of the 20th Century. To understand the process, it was used the Thematic Oral History, a methodology that allows to view the present as a continuation of the past. 11 professionals who have actively participated in the process were interviewed as coordinators and teachers in obstetric nursing graduate specializations, as members of Ministry of Health Woman Health Theme area and Brazilian Association of Obstetricians. Among the factors that contributed with the research we can mention the Ministerial policies, financing of graduate specializations, the continuity of the professionals’ performances, and the creation of Normal Birth Centers. It was concluded that the acknowledgement of those professionals work depend on the graduation and quality performance and that it is necessary to carry out more research on such performances and publish their results.